Pseudocapacitance-boosted ultrafast Na storage in a pie-like FeS@C nanohybrid as an advanced anode material for sodium-ion full batteries. Issue 19 (4th May 2018) - Hou, Bao-Hua; Wang, Ying-Ying; Guo, Jin-Zhi; Ning, Qiu-Li; Xi, Xiao-Tong; Pang, Wei-Lin; Cao, An-Min; Wang, Xinlong; Zhang, Jing-Ping; Wu, Xing-Long
Abstract : A novel pie-like FeS@C nanohybrid has been prepared, which exhibits pseudocapacitance-prompted ultrafast Na storage and superior Na-ion full-cell performance. Abstract : In order to develop promising anode materials for sodium-ion batteries (SIBs), a novel pie-like FeS@C (P-FeS@C) nanohybrid, in which all ultrasmall FeS nanocrystals (NCs) are completely embedded into the carbon network and sealed by a protective carbon shell, has been prepared. The unique pie-like structure can effectively speed up the kinetics of electrode reactions, while the carbon shell stabilizes the FeS NCs inside. Studies show that the electrochemical reaction processes of P-FeS@C electrodes are dominated by the pseudocapacitive behavior, leading to an ultrafast Na + -insertion/extraction reaction. Hence, the prepared P-FeS@C nanohybrid exhibits superior Na-storage properties especially high rate capability in half cells. For example, it can deliver reversible capacities of 555.1 mA h g −1 at 0.2 A g −1 over 150 cycles and about 60.4 mA h g −1 at 80 A g −1 (an ultrahigh current density even higher than that of the capacitor test). Furthermore, an advanced P-FeS@C//Na3 V2 (PO4 )2 O2 F full cell has been assembled out, which delivers a stable specific capacity of 441.2 mA h g −1 after 80 cycles at 0.5 A g −1 with a capacity retention of 91.8%.